Virtual Reality-Integrated Immersion-Based Teaching to English Language Learning Outcome - Xie, Yu; Liu, Yang; Zhang, Fengrui; Zhou, Ping (Frontiers in Psychology, 2022)
Globalization and informatization are reshaping human life and social behaviors. The purpose is to explore the worldwide strategies to cultivate international talents with a global vision. As a global language with the largest population, English, and especially its learning effect, have always been the major concerns of scholars and educators. This paper innovatively studies the combination of immersion-based English teaching with Virtual Reality (VR) technology. Then, based on the experimental design mode, 106 students from a Chinese school are selected for a quasi-experimental study for 16 weeks (3 hours a week, and 48 hours in total). The collected data are analyzed by computer statistical software, and hypotheses are verified. The results show that there is a significantly positive correlation between VR and immersion-based language teaching (0.851, p<0.01); there is a significantly positive correlation between immersion-based language teaching and academic achievement (0.824, p<0.01); VR is positively correlated with Learning Outcome (LO) (0.836, p<0.01). Compared with other state-of-art research methods, this paper modifies the students' oral test through the analysis and comparison with the system database, and the students' learning effect is greatly improved. Finally, some suggestions are put forward according to the research results to provide an experimental reference for English teachers and future linguistics teaching.